RETHINKING IMAM ABU HANIFAH’S JURISPRUDENCE AND THE GLOBAL DISSEMINATION OF MODERATE ISLAM - Rizapoor, Habiburrahman; Rahimi, Mohammad Rashid (State Islamic University North Sumatra, 2023)
Abstract: This article examines the role of Imam Abu Hynifah in the spread of moderate Islam. Through an analytical and descriptive research approach, the study investigates whether Imam Abu Hynifah can be considered one of the leading scholars in Wasatiah Islam and explores the impact of his views on the spread of moderate Islamic teachings around the world. The research draws on a variety of sources, including books, Imam Abu Hynifah’s writings, and relevant articles from academic journals. This article presents a comprehensive analysis of Imam Abu Hynifah’s views and contributions to Islamic jurisprudence. It explores the basic principles of his madhhab and highlights the moderation inherent in his interpretation of Islamic law.Keywords: Imam Abu Hanifah, Al-Islam Al-Wasatiyyah, Al-Madhhab Al-Hanafi, Al-Islam Al-Mu’tadil